CADAR BAGI WANITA MUSLIMAH DALAM PERSPEKTIF HUKUM ISLAM - Muh. Sudirman (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
The veil is a name that is intended for clothes that serve to cover the face for women from the nose or from under the curve of the eye down. The order of wearing veils for Muslim women is not explicitly explained either in the Qur'an or in the Prophet's hadith. What the Islamic Syari'ah orders for women is wearing the hijab. The law of wearing veils for Muslim women is a mubah instead of a must and not a mustahab, and it is a right for a Muslim to get used to it, and it can not be for a person to forbid it, because it is just exercising her privileges. Moreover, in getting used to or wearing it does not damage something that is obligatory and does not harm others.